The Impact of Artificial Intelligence on Human Workers - akhmad farhan (Journal Of Communication Education, 2023)
The impact of artificial intelligence on human workers is a complex and ongoing topic of research and debate, and the extent to which AI will replace human jobs is still uncertain. Therefore, this research aims to answer following research questions. How does artificial intelligence affect human workers? What jobs will be replaced by artificial intelligence? What jobs can endure without being replaced by artificial intelligence?. This research was conducted in qualitative approach based on secondary data from previous studies. Data analysis techniques through four stages, namely data collection, data reduction, data presentation and drawing conclusions. After reviewing the remaining articles for eligibility in terms of the inclusion criteria, 45 papers were included in the data analysis. This study conclude that artificial intelligence has the ability to augment human talents, generate innovation, offer new career possibilities, and improve decision-making. Adopting AI technologies not only improves employee skills and productivity, but also enables organizations to function more efficiently. This study found that the negative effects of AI, such as job displacement, lower labour demand, employee deskilling, erosion of privacy and autonomy, exacerbation of wealth inequality, and shifting employee requirements. AI has the potential to disrupt traditional work functions in routine and repetitive tasks, manual labour, high-paying occupations, decision-making roles, HR operations, and certain service industry jobs. AI struggles to imitate creative endeavours, emotional intelligence, physical dexterity, human interaction, and complicated decision-making. These professions will continue to thrive as technology advances, reminding us that the essence of human experience is irreplaceable.